The Separatist Movements: A Review of The Conflict Between Self-Determination, State Sovereignty and International Law - Khoirunnisa, Khoirunnisa; Jubaidi, Didi (Jurnal Polinter : Kajian Politik dan Hubungan Internasional, 2025)
Separatism is a complex and sensitive issue in the context of international law and human rights. This research aims to explore the correlation between self-determination and human rights in relation to separatist movements, with a focus on the conflicts that arise between state sovereignty and international law. The article also analyzes several case studies of separatist conflicts in various regions to provide a more concrete understanding. The research methodology employed is a normative juridical approach, utilizing literature review from diverse sources such as books, online media, dissertations, and other relevant literature. The research findings confirm that self-determination is recognized as a human right in international law. This right allows ethnic, national, or regional groups to determine their own destiny, including the option of secession from an existing state and in the national law of Indonesia, the right to self-determination is interpreted in the context of regional autonomy. However, conflicts arise when the implementation of self-determination contradicts the principle of state sovereignty. The separatist movement involves complex correlations between self-determination, human rights, state sovereignty, and international law. Sustainable conflict resolution requires a balanced and comprehensive approach that recognizes and protects human rights without disregarding the principle of state sovereignty.